Pharmacological Properties, Central Nervous System Effects, and Potential Therapeutic Applications of Atipamezole, a Selective α2‐Adrenoceptor Antagonist - Pertovaara, Antti; Haapalinna, Antti; Sirviö, Jouni; Virtanen, Raimo (CNS drug reviews, 2005)
ABSTRACT Atipamezole is an α2‐adrenoceptor antagonist with an imidazole structure. Receptor binding studies indicate that its affinity for α2‐adrenoceptors and its α2/α1 selectivity ratio are considerably higher than those of yohimbine, the prototype α2‐adrenoceptor antagonist. Atipamezole is not selective for subtypes of α2‐adrenoceptors. Unlike many other α2‐adrenoceptor antagonists, it has negligible affinity for 5‐HT1A and I2 bindings sites. Atipamezole is rapidly absorbed and distributed from the periphery to the central nervous system. In humans, atipamezole at doses up to 30 mg/subject produced no cardiovascular or subjective side effects, while at a high dose (100 mg/subject) it produced subjective symptoms, such as motor restlessness, and an increase in blood pressure. Atipamezole rapidly reverses sedation/anesthesia induced by α2‐adrenoceptor agonists. Due to this property, atipamezole is commonly used by veterinarians to awaken animals from sedation/anesthesia induced by α2‐adrenoceptor agonists alone or in combination with various anesthetics. Atipamezole increased sexual activity in rats and monkeys. In animals with sustained nociception, atipamezole increased pain‐related responses by blocking the noradrenergic feedback inhibition of pain. In tests assessing cognitive functions, atipamezole at low doses has beneficial effects on alertness, selective attention, planning, learning, and recall in experimental animals, but not necessarily on short‐term working memory. At higher doses atipamezole impaired performance in tests of cognitive functions, probably due to noradrenergic overactivity. Recent experimental animal studies suggest that atipamezole might have beneficial effects in the recovery from brain damage and might potentiate the anti‐Parkinsonian effects of dopaminergic drugs. In phase I studies atipamezole has been well tolerated by human subjects.